EPIDEMIOLOGY OF TRAFFIC TRAUMATISM - Peličić, Damir; Ristić, Branko; Radević, Svetlana (Sanamed, 2024)
Through a review of relevant literature, we provide insight into the public health issue of traffic trauma both globally and locally. According to estimates by the World Health Organization (WHO), approximately 1.35 million people die annually in traffic accidents, while nearly 50 million suffer minor or severe injuries. Globally, traffic injuries account for about 2.37% of all deaths, ranking eighth among all causes of death. The Global Status Report on Road Safety 2018 indicates that the number of traffic deaths did not decrease in any low-income country between 2013 and 2016, although a reduction was observed in 48 middle- and high-income countries during that period. Despite the increase in absolute numbers, the global road traffic mortality rate has remained fairly constant at around 18 deaths per 100 000 inhabitants over the past 15 years, with the highest rate in the African region and the lowest in the European region. Currently, traffic accidents are the leading cause of death among children and young adults aged 5 to 29 years, with a higher incidence among males. Further research is needed to better understand the specific characteristics of traffic injuries in the local population and to identify the most effective intervention programs.
Keywords: trauma; trauma registry; polytrauma; public health